2009
DOI: 10.1007/s11214-009-9580-z
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetic Records of Meteorites and Early Planetesimal Differentiation

Abstract: The large-scale compositional structures of planets are primarily established during early global differentiation. Advances in analytical geochemistry, the increasing diversity of extraterrestrial samples, and new paleomagnetic data are driving major changes in our understanding of the nature and timing of these early melting processes. In particular, paleomagnetic studies of chondritic and small-body achondritic meteorites have revealed a diversity of magnetic field records. New, more sensitive and highly aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
146
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 143 publications
(168 citation statements)
references
References 218 publications
(300 reference statements)
8
146
2
Order By: Relevance
“…In contrast to the assumption of Hevey & Sanders (2006) that the parent bodies of differentiated meteorites formed prior to the accretion of the most chondritic parent bodies, our results indicate that both chondritic meteorites and differentiated meteorites can originate from one and the same parent body. This finding is consistent to the results of Weiss et al (2010) and Elkins-Tanton et al (2011), where a differentiated interior is covered with undifferentiated crust to explain the remanent magnetisation of the CV meteorite Allende.…”
Section: Summary and Discussionsupporting
confidence: 91%
“…In contrast to the assumption of Hevey & Sanders (2006) that the parent bodies of differentiated meteorites formed prior to the accretion of the most chondritic parent bodies, our results indicate that both chondritic meteorites and differentiated meteorites can originate from one and the same parent body. This finding is consistent to the results of Weiss et al (2010) and Elkins-Tanton et al (2011), where a differentiated interior is covered with undifferentiated crust to explain the remanent magnetisation of the CV meteorite Allende.…”
Section: Summary and Discussionsupporting
confidence: 91%
“…The very high NRM to saturation IRM ratio of this component (0.23) indicates that it is an IRM acquired during exposure to artificial fields. The maximum unblocking coercivity suggests that the artificial field had a maximum intensity of ~30 mT (84), which is consistent with a weak hand magnet (38). Furthermore, the presence of the LCb overprint only in samples from local area within 2 mm of the sample edge is expected for an origin due to contact with a hand magnet.…”
Section: The Lcb Overprintsupporting
confidence: 56%
“…However, because the Lanoix et al (36) study measured unoriented chondrules, the authors were unable to demonstrate a pre-accretional origin for the observed magnetization (see Section 3.4). In fact, the very high paleointensities and the failure of later experiments to duplicate these results strongly indicate that the purported pre-accretional magnetization component studied in Lanoix et al (36) was due to contamination by strong artificial magnetic fields (e.g., from hand magnets) and does not offer constraints on nebular magnetic fields (37,38).…”
Section: Previous Searches For Nebular Magnetic Fieldsmentioning
confidence: 93%
“…The scaling law based on energy flux provides a handle for estimates of the strength of Earth's paleofield (Aubert et al 2009) and for the magnetic fields of now extinct dynamos, for example in early Mars or in large differentiated asteroids (Weiss et al 2008(Weiss et al , 2009. It also allows to estimate the magnetic field strength of extrasolar planets.…”
Section: Discussion and Outlookmentioning
confidence: 99%